PENGARUH KARAKTERISTIK KELOMPOK DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA KARYAWAN CV. CROSSLINE PRODUCTION PALEMBANG - N Noviarni; K Kartawinata (Fakultas Ekonomi Universitas Tridinanti Palembang, 2020)
This research is basically discuss the influence of group characteristic and work characteristic on employee performance at CV. Crossline Production Palembang by using quantitative data analysis which are correlation coefficient analysis, coefficient of determination, hypotheses testing of statistic t-tests, and statistic F-tests. The sample of this research is all the employees of CV. Crossline Production Palembang, that are 30 people.Regression coefficient value for competency variable (X1) is 0,001 and work culture variable (X2) is 0,000 with level of significance 5%, these produce constant value at 1,190. So, the regression equation used in this research isY = 1,190 + 0,255x1 + 0,726x2 + e.The test result in this research indicate that group characteristic and work characteristic have positive effect on employee performance simultaneously. Those independent variables have effect too on employee performance partially. The amount of coefficient of determination (Adjusted R Square) at 0,831 show that independent variables (group characteristic and work characteristic) have effect on dependent variable (employee performance) at 83,1%, while the rest is effected by other variables that are not use in this research. Keywords:Characteristic,Employee, Performance